Venom of the neotropical rattlesnake, Crotalus culminatus: Intraspecific variation, neutralization by antivenoms, and immunogenicity in rabbits - Zarzosa, Vanessa (2023)
Crotalus culminatus is a medically significant species of rattlesnake in Mexico [1]. While the proteomic composition of its venom has been previously reported for both juvenile and adult specimens, there has been limited research into its functional properties, with only a few studies, including one focusing on coagulotoxicity mechanisms. In this study, we aimed to compare the biochemical and biological activities of the venom of juvenile and adult snakes. Additionally, we assessed antibody production using the venoms of juveniles and adults as immunogens in rabbits. Our findings reveal lethality and proteolytic activity differences between the venoms of juveniles and adults. Notably, juvenile venoms exhibited high proportions of crotamine, while adult venoms displayed a reduction of this component. A commercially available antivenom demonstrated effective neutralization of lethality of both juvenile and adult venoms in mice. However, it failed to neutralize the paralytic activity induced by crotamine, which, in contrast, was successfully inhibited by antibodies obtained from hyperimmunized rabbits. These results suggest the potential inclusion of C. culminatus venom from juveniles in commercial antivenom immunization schemes to generate antibodies targeting this small myotoxin.